2012
DOI: 10.1007/s10597-012-9516-z
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Low-Intensity Home-Based Aftercare for Patients with Severe Mental Disorders: A 12-month Randomized Controlled Study

Abstract: To examine the effectiveness of a low-intensity home-based aftercare service, 130 patients with schizophrenia, schizoaffective disorder or bipolar disorder were randomized to receive either home aftercare or treatment-as-usual. In home aftercare, a general practitioner and a social worker made home visits once in a month after discharge from the hospital wherein they provided education and treatment. In a 1-year follow-up, home aftercare led to greater reduction in rehospitalization rate, more improvement in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
54
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(59 citation statements)
references
References 18 publications
1
54
0
4
Order By: Relevance
“…However, more GP treatment time was found to increase the risk for rehospitalisation in one study [52], while just being registered with a primary care unit did not make a significant difference in another [33]. In a randomized controlled study, Sharifi et al found that when a GP and a social worker made home visits once during the month after discharge from the hospital wherein they provided education and treatment (home aftercare), it led to a reduction in rehospitalisation rate [53]. Similar results were obtained when the home visits were conducted by psychiatric nurses only [54, 55].…”
Section: Resultsmentioning
confidence: 99%
“…However, more GP treatment time was found to increase the risk for rehospitalisation in one study [52], while just being registered with a primary care unit did not make a significant difference in another [33]. In a randomized controlled study, Sharifi et al found that when a GP and a social worker made home visits once during the month after discharge from the hospital wherein they provided education and treatment (home aftercare), it led to a reduction in rehospitalisation rate [53]. Similar results were obtained when the home visits were conducted by psychiatric nurses only [54, 55].…”
Section: Resultsmentioning
confidence: 99%
“…); Their findings on clinical efficacy showed a similar reduction in re‐hospitalisation, psychotic and depressive symptoms as well as an increase in clinical global impression (Sharifi et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…The development of AFTH could facilitate alignment with those international recommendations through two main mechanisms. First, previous international research has shown the benefit of AFTH, in particular in terms of increased quality of life, clinical outcomes, adherence to treatment, accessibility and continuity of care [27,28,29,30,31,32,33]. This suggests that AFTH have the potential to decrease patients’ severity of illness through increased quality of care.…”
Section: Introductionmentioning
confidence: 99%